Synthesis of unnatural α-amino esters using ethyl nitroacetate and condensation or cycloaddition reactions - Gagnot, Glwadys; Hervin, Vincent; Coutant, Eloi P.; Desmons, Sarah; Baatallah, Racha; Monnot, Victor; Janin, Yves L. (Beilstein Journal of Organic Chemistry, 2018)
We report here on the use of ethyl nitroacetate as a glycine template to produce α-amino esters. This started with a study of its condensation with various arylacetals to give ethyl 3-aryl-2-nitroacrylates followed by a reduction (NaBH4 and then zinc/HCl) into α-amino esters. The scope of this method was explored as well as an alternative with arylacylals instead. We also focused on various [2 + 3] cycloadditions, one leading to a spiroacetal, which led to the undesired ethyl 5-(benzamidomethyl)isoxazole-3-carboxylate. The addition of ethyl nitroacetate on a 5-methylene-4,5-dihydrooxazole using cerium(IV) ammonium nitrate was also explored and the synthesis of other oxazole-bearing α-amino esters was achieved using gold(I) chemistry.
Keywords: α-amino ester; α-nitro esters; cerium ammonium nitrate; cycloaddition; gold(I) cyclization